2017
DOI: 10.3892/ijo.2017.3868
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 is correlated with the malignancy of non-small cell lung cancer

Abstract: The mitochondrial deacetylase SIRT3 plays a pivotal role in the initiation and the progression of certain cancers acting as an oncogene. However, in others it acts anti-oncogenically. Its conflicting action is possibly due to the different key proteins it modifies depending on the context of active intracellular signaling pathways in different cancers. SIRT3 is thus a novel target for preventing and treating cancer. In the present study, we explored the function of SIRT3 in non-small cell lung cancer (NSCLC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Pannoramic 250/ MIDI (3DHISTECH) was used to scan and digitalize the slides. Pannoramic Viewer v. 2.0 and NuclearQuant application for PV v.2.0.0.46136, both of which are manufactured by 3DHISTECH, were used to analyze the slides 30. …”
mentioning
confidence: 99%
“…Pannoramic 250/ MIDI (3DHISTECH) was used to scan and digitalize the slides. Pannoramic Viewer v. 2.0 and NuclearQuant application for PV v.2.0.0.46136, both of which are manufactured by 3DHISTECH, were used to analyze the slides 30. …”
mentioning
confidence: 99%
“…Moreover, the role and putative mechanism of Sirt3 in chronic stroke are also unknown. Previous studies have shown that downregulation of Sirt3 decreased the activation of AKT which is involved in neurogenesis and angiogenesis, and Sirt3 is essential for apelin‐mediated angiogenesis in postmyocardial infarction of diabetes . Rehabilitation after ischemic stroke requires the recovery of neural, vascular, and connective tissue components in the damaged brain region; our previous study showed that Sirt3 could mediate the inhibitory effect of adjudin on glial scar formation which was correlated with neural functional recovery following ischemic stroke .…”
Section: Introductionmentioning
confidence: 83%
“…Nicotine-mediated cancer progression is mediated by nicotine/nAChRs signaling. By contrast to the tumor-suppressing role of SIRT2/4, the roles of SIRT1/6/7 and mitochondrial SIRT3/5 are strongly associated with drug resistance in lung cancer [119,120,124,135,142,144,146,[150][151][152][153][154]. However, SIRT1/2 inhibitor, sirtinol, can increase anticancer potential and chemosensitivity in several cancer cells [102,160,161].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3, located in mitochondria, is correlated with NSCLC malignancy [142]. α7nAChRs activation inhibits platelet-derived growth factor-induced cells migration by activating the mitochondrial deacetylase SIRT3, implying a critical role for α7nAChRs in mitochondrial biology and PDGF-related diseases [143].…”
Section: Sirt2-sirt7mentioning
confidence: 99%
See 1 more Smart Citation